Family Participation in The Integrated Management of Childhood Illness Implementation Process: Systematic Literature Review - Joaquim Pinto; Yenny Puspitasari (Journal of International Multidisciplinary Research, 2024)
This study aims to analyze the role and contribution of families in the implementation of Integrated Management of Childhood Illness (IMCI) and the impact of family participation on child health outcomes. In addition, this study also identified factors that support or hinder family participation in the IMCI program. The method used was a systematic literature review of various published studies. The method used is a systematic literature review with the main data source of 15 previous studies on the theme to be examined in this study so that the data makes a new finding. The main findings of this study show that family education, social and community support, health policies, and family experiences and perceptions of IMCI are important themes that influence the successful implementation of IMCI. Effective education of families improves their understanding and skills in managing childhood illnesses, while support from health workers and the community can increase family participation in IMCI programs. Supportive health policies and appropriate interventions also play an important role in ensuring the program's effectiveness. However, lack of motivation and adequate information from health workers can be barriers to family participation. This study confirms the importance of active family participation in IMCI implementation to improve child health outcomes. Recommendations for further research include evaluation of the most effective educational methods, the influence of technology in supporting IMCI, and longitudinal studies to monitor the long-term impact of family participation. From a health policy perspective, improved training for health workers, strengthened social and community support networks, and improved accessibility of health information through various media are suggested to support better implementation of IMCI programs.